The risks factor affecting the returns of corporate bonds: evidence from construction and properties sector in Malaysia / Erra Farida Mohamad - Mohamad, Erra Farida (2018)
Corporate bond yield or return is an important element in the corporate bond market especially for the bond holders as well as for those who are investing in the corporate bond market. Some of these investors and bond holders may be afraid of the risk they will face in this corporate bond market because of the “thin market” that occurs at times in which the bonds are being traded infrequently. In order to determine whether these bond holders and investors in the corporate bond market earn a significant return or not, this is the main reason why this study is being conducted. This study aims to investigate whether risk such as liquidity risk, credit risk and financial leverage or leverage risk affects the yield or the return of corporate bond for companies under the properties and construction sector, with the total of 47 companies. The dependent variable is the corporate bond return itself, whereas the independent variables are measured by the bid-ask spread for liquidity risk, interest coverage ratio for credit risk and the debt to equity ratio for financial leverage. The study period of this study is from 2011 to 2015. Using the software STATA12 package to run the data, the multiple linear regressions analysis is being used to determine the effect of the independent variables towards the dependent variable. Based on the findings, for both properties and construction sector, liquidity risk measured by bid-ask spread do have a significant effect towards the corporate bond return.